Oxidative Distress and Its Correction with Reamberin in Patients With Acute Poisoning by a Mixture of Psychotropic Substances - G. A. Livanov; B. V. Batotsyrenov; S. A. Vasilyev; A. Yu. Andrianov; D. V. Baranov; I. V. Nezhentseva (Общая реаниматология)
Objective: to determine the impact of reamberin incorporation into intensive care on the antioxidant defense system and the activity of lipid peroxidation in patients with toxic-hypoxic encephalopathy. Subjects and methods. The investigation enrolled 84 patients with acute severe poisoning by a mixture of psychotropic substances (hypnotics, neuroleptics, antidepressants, 1,4-benzodiazepine derivatives, ethanol). Oxygen balance parameters (oxygen consumption, oxygen utilization quotient, and arteriovenous oxygen difference) were calculated. The antiradical defense system was evaluated determining the levels of reduced glutathione and free sulfhydryl groups of proteins activity of the antiradical enzymes glutathione peroxidase, glutathione-S-transferase, and catalase in red blood cells. Lipid peroxidation rate in red blood cells was determined by measuring the concentration of malondialdehyde. Results. The incorporation of reamberin into intensive care was found to be accompanied by a reduction in tissue hypoxia, more rapid recovery of the antioxidant defense system, and a decrease in the activity of lipid peroxidation processes. Сorrection of metabolic disturbances in its turn leads to the improved clinical course of acute poisoning, which manifests itself as a reduction in the duration of coma, the length of stay in the intensive care unit, and mortality. Conclusion. The reduction in the severity of metabolic disturbances associated with the development of hypoxia and free radical disorders leads to substantial improvement of the clinical course and outcomes of toxic-hypoxic encephalopathy. Key words: toxic-hypoxic encephalopathy, hypoxia, antioxidant system, lipid peroxida-tion, reamberin.